Importance of Lignin on the Properties of Binderless Particleboard Made From Oil Palm Trunk - Boon, Jia Geng; Rokiah, Hashim; Othman, Sulaiman; Sugimoto, Tomoko; Sato, Masatoshi; Nurjannah, Salim; M. H. M., Amini; Sitti Fatimah, M. R.; Nor Izaida, Ibrahim (Asian Research Publishing Network (ARPN)., 2017)
This study investigated the influence of soda lignin extracts from oil palm on the binderless particleboard properties especially in against moisture. Characterization analysis of oil palm soda lignin, including carbon, hydrogen, nitrogen, sulphur elemental analysis, ash content, infrared spectra via fourier transform spectrometer, glass transition point, and thermal decomposition were conducted. Moisture resistant properties including thickness swelling, and dimensional changes with changes of relative humidity of binderless board with lignin add-on were investigated. Mechanical strength properties including modulus of rupture and internal bond strength were evaluated. Scanning electron microscopy image of specimens was inspected. Lignin was statistically significant influencing the properties of oil palm binderless particleboard. All specimens with lignin added showed better performances than control specimens that without lignin add-on. Binderless board with 5% lignin add-on showed the best result in moisture resistant properties and mechanical properties.